Finite element analysis of hybrid energy harvesting of Piezoelectric and electromagnetic - Muhammad Ammar Faris, Muhammad Yazid (2016)
Harvesting energy from ambient vibrations is a highly sought after method because of the wide range of available sources that produce vibration energy applicable from industrial machinery to human motion application. This report studied the implementation of harvesting energy from two technologies to form a hybrid energy harvester system. These two technologies involves are relate to the piezoelectric harvesting energy as well as the electromagnetic harvesting energy. A finite element model was developed by using the Ansys software with the harmonic analysis solver to analyze and examine hybrid harvesting energy system. The variance dimension of geometry on the bimorph piezoelectric cantilever beam is also being implemented in order to study the performance of the beam relating to the difference perspective of dimension. The proposed length of the cantilever beam was 16.5mm and 36.5mm with the width of 6.35mm, 12.7mm, and 19.05mm. Both power output generated from the magnet and the piezoelectric is then combined to form one unit of energy. The result shows the system generate the maximum power output of 14.85